Gambaran motivasi berprestasi pada mahasiswa setelah mengikuti program Pertukaran Mahasiswa Merdeka (PMM) - Rahman, Yunita; Wafa, Iqbal Ali (UIN Maulana Malik Ibrahim Malang, 2024)
The Student Exchange Program influences student achievement motivation. The article explains that after participating in the program it brings achievement motivation to students. The participants in this study were four students. This study uses the phenomenological method. This data collection uses four steps: interview transcripts, koding, categorization, and sub-theme conclusions. The results of this study found that, First, how the experience can encourage various aspects such as reinforcement and self-confidence in achievement motivation. Second, these things become achievement motivation that shape the process of self-development in students to develop talents. Third, how the program becomes a motivating factor for students to achieve achievements by having high responsibility, taking risks, and existence in lifeKEY WORDS: Achievement motivation; reinforcements; develop talent ABSTRAKProgram Pertukaran Mahasiswa mempengaruhi motivasi berprestasi mahasiswa. Dari artikel menjelaskan kalau setelah mengikuti program tersebut membawa motivasi berprestasi pada mahasiswa. Partisipan dalam penelitian ini berjumlah empat mahasiswa. Penelitian ini menggunakan metode fenomenologi. Pengumpulan data ini menggunakan empat langkah: transkrip wawancara, koding, kategorisasi, dan kesimpulan sub-tema. Hasil dari penelitian ini menujukkan bahwa, Pertama, bagaimana pengalaman tersebut dapat mendorong berbagai aspek seperti reinforcement dan kemampuan percaya diri dalam motivasi berprestasi. Kedua, hal-hal tersebut menjadi motivasi berprestasi yang membentuk proses pengembangan diri pada mahasiswa untuk mengembangkan bakat. Ketiga, bagaimana program tersebut menjadi faktor pendorong bagi mahasiswa untuk meraih prestasi dengan memiliki tanggung jawab yang tinggi, megambil risiko, dan eksistensi hidupKATA KUNCImotivasi berprestasi; penguatan; mengembangkan bakat Copyright ©2024. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. link: CreativeCommons — Attribution-NonCommercial-ShareAlike 4.0 International — CCBY-NC-SA 4.0